International Scientific Conference “Grammar of Meletius Smotritsky in the Linguistic Context of Europe of the 16th – 18th centuries”. - Konickaja, Jelena (Slavistica Vilnensis, 2019)
International Scientific Conference “Grammar of Meletius Smotritsky in the Linguistic Context of Europe of the 16th – 18th centuries”. (Vilnius, September 29–October 2, 2019)